Improvement of the technology of the gas treatment by the condensation method - Летюк, Євген Олександрович (Technology audit and production reserves, 2014)
Natural gas treatment for transport using the condensation method is considered in the paper. The main objective of the study is to examine the possibilities of decreasing the amount of low-pressure gases, produced when reducing hydrocarbon condensate, separated from natural gas, to the standard conditions. Decreasing the amount of these gases becomes possible due to introducing a portion of the treated natural gas in a gas-liquid flow before the final stage separator in the gas treatment plant. Thus, the portion of low-boiling components, constituting the treated natural gas in the gas phase increases. This leads to the decrease in the low-boiling components solubility in the hydrocarbon condensate and thereby clearer gas components separation into the low-boiling and high-boiling components, which form the hydrocarbon condensate. The calculation results of the technological scheme of gas treatment plant, the operation of which is based on the proposed method are given in the paper. Calculations show the possibility of reducing the amount of low-pressure gases by 10%, which in turn reduces the energy consumption for recycling these gases. The proposed method for decreasing the amount of low-pressure gases, formed when reducing the hydrocarbon condensate to the standard conditions can be used in gas treatment plants.